Prevalence and pathological investigation of fowl typhoid in commercial poultry farms at the Rajshahi City Corporation area of Bangladesh - Siddique, Abu Bakkar; Khaton, Rashida (Research in Agriculture Livestock and Fisheries, 2021)
The present study was conducted to determine the prevalence of Fowl typhoid in apparently healthy, sick and dead birds at Rajshahi city corporation area of Bangladesh. A total of 500 birds (50 from each farm) and 30 different organs (liver from 10, ovary from 8, heart from 7, and caecal tonsils from 5) were randomly collected from different commercial poultry farms during the period from January 2018 to December 2018. The prevalence study was performed based on history, clinical signs, symptoms exhibited by the individual bird of a flock during the observation of farms, and illness of birds. The suspected birds were subjected to necropsy examination. During sample collection, clinical signs and gross necropsy changes were recorded very carefully. The collected tissues were fixed, processed, sectioned, stained, and studied light microscopically. The routine histopathological method was used for the detection of tissue-level alterations in Fowl typhoid infected cases. The prevalence of Fowl typhoid in apparently healthy birds of different poultry farms was 8.2%, and 23.33% of organs were involved. Grossly, the liver was enlarged, congested and revealed bronze discoloration with focal necrosis in the surface of the liver. Old raised hemorrhages were found in the caecal tonsils. Congested, deformed, and pedunculated ova were other important findings. Microscopically, the sections of the liver showing multifocal necrosis with infiltration of heterophils and reticulo-endothelial cells. Res. Agric., Livest. Fish.8(2): 201-209, August 2021